Liraglutide Decreases Liver Fat Content and Serum Fibroblast Growth Factor 21 Levels in Newly Diagnosed Overweight Patients with Type 2 Diabetes and Nonalcoholic Fatty Liver Disease - Xinyue Li; Xiaojuan Wu; Yumei Jia; Jing Fu; Lin Zhang; Tao Jiang; Jia Liu; Guang Wang (Journal of Diabetes Research)
Purposes. In this study, we aimed to verify plasma fibroblast growth factor 21 (FGF21) elevation in newly diagnosed overweight patients with type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD) and to evaluate the effectiveness of liraglutide on reducing liver fat content and serum (FGF21) levels in those patients. Methods. A 12-week, single-center, prospective study was conducted. Twenty newly diagnosed overweight patients with T2DM and NAFLD were recruited. Twenty healthy age, sex, and body mass index (BMI) matched subjects were enrolled as the control group. Enzyme-linked immunosorbent assay was used to measure serum FGF21 levels. Liver fat content was determined using the 3.0 T whole-body MRI scanner. Results. Those newly diagnosed overweight patients with T2DM and NAFLD had a BMI of 27.6±0.5 kg/m2. They had higher levels of FGF21 (159.6±35.7 vs. 124.1±42.9 pg/ml, P<0.001) and increased liver fat content (19.3±9.4 vs. 4.5±0.6%, P<0.001) compared to the controls. Liraglutide treatment for 12 weeks induced a significant 4.9 kg weight loss (95% confidence interval (CI): -6.1, -3.7, P<0.001), which was equivalent to a relative reduction of 6.8% (95% CI: 5.3%, 8.3%, P<0.001). FGF21 levels decreased after the 12-week liraglutide treatment (159.6±35.7 vs. 124.2±27.8 pg/ml, P=0.006). There was a positive correlation between relative changes of liver fat content and relative change of FGF21 (r=0.645, P=0.002). FGF21 levels significantly decreased in patients who had a significant decrease in liver fat content (≥29%) (95% CI: -262.8, -55.1, P=0.006); however, there was no significant change in the patients without a significant decrease in liver fat content (<29%) (95% CI: -60.0, 54.1, P=0.899). Conclusions. Liraglutide treatment reduced both liver fat content and FGF21 levels in newly diagnosed overweight patients with T2DM and NAFLD. FGF21 may be a potential biomarker for evaluating the effects of liraglutide treatment on hepatic fat and glucose metabolism.